Enkele wijsgerige en (ideeën)historische aanzetten tot een nieuwe verhouding tussen de sferen van het private, het publieke en het heilige - Labuschagne, Bart (Religie & Samenleving, 2011)
Current debates on the place of religion in society in relation to politics and law tend to view religion as something that has only meaning in the private sphere or also maybe in some way in the public realm. In order to do more justice to what religion is, a plea is developed in this contribution to discern and explore a dimension beyond the private and public, that is: the domain of the sacred. Inspired by the work of Eric Voegelin, the history and the experience of ancient Israel, early Christianity and early Reformation, the relevance is shown of a distinction of the sacred realm vis-à-vis the domains of the public and the private. This new paradigm enables us to look critically at tendencies that can be discerned among believers of different religions (for example in Islam) as well as non-believers (for example in Secularism). By distinguishing between these domains, one can avoid both the sacralisation of the public domain (totalitarianism) and the sacralisation of the private realm (sectarianism or even hedonism).